Phase II randomized study on tissue distribution and pharmacokinetics of cisplatin according to different levels of intra-abdominal pressure (IAP) during HIPEC (NCT02949791). Issue 1 (January 2021) - Kusamura, Shigeki; Azmi, Norfarizan; Fumagalli, Luca; Baratti, Dario; Guaglio, Marcello; Cavalleri, Adalberto; Garrone, Giulia; Battaglia, Luigi; Barretta, Francesco; Deraco, Marcello
Abstract: Aims: To evaluate the effects of high intra-abdominal pressure (IAP) during hyperthermic intraperitoneal chemotherapy (HIPEC) on cisplatin uptake by residual tumor and normal tissues, pharmacokinetics, and short-term surgical outcomes. Patients & methods: Patients with peritoneal metastasis from colorectal cancer or pseudomyxoma peritonei were randomized to closed-abdomen HIPEC with low-IAP or high-IAP, after complete cytoreduction. High-IAP was obtained increasing the volume of perfusate maintaining constant the cisplatin concentration (42 mg/L). We determined the Platinum concentration using an Inductive Coupled Plasma Mass Spectrometry System. Randomization was stratified according to tumor type. To consider the multiple sampling in the three tissues types of interest, we performed linear mixed models to assess the differences of cisplatin concentration between study arms. We also compared AUC perfusate/plasma ratios (Wilcoxon-Mann-Whitney) and perioperative severe complication rates (chi-square) between study arms. Results: 38 cases were randomly assigned to IAP arms (n = 19 each). Median IAPs were 19 mmHg and 11 mmHg in the high and low arms, respectively. Cisplatin concentrations did not differ in the tumor residual tissues and in the muscular fascia [22.8 ng/mg (SD: 25.5) vs. 15.9 ng/mg (SD: 13.3), p = 0.181] and [50.3 ng/mg (SD: 40.1) vs. 42.0 ng/mg (SD: 38.3), p = 0.426, respectively], whereas in the mesenteric peritoneum it did [5.4 ng/mg (SD: 7.82) vs. 2.7 ng/mg (SD: 2.9), p = 0.048]. Pharmacokinetic advantage did not differ between the two arms. High-IAP did not increase perioperative severe complications rate (NCI-CTCAE.v3). Conclusions: high-IAP HIPEC increases cisplatin distribution in the mesenteric peritoneum, is safe, and could be considered to obtain microscopic cytoreduction.